CORPORATE GOVERNANCE OF JOINT-STOCK COMPANIES WITH STATE PARTICIPATION: CIVIL-LAW ASPECTS AND REFORM IN UZBEKISTAN (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The article examines the corporate governance of joint-stock companies with state participation as a civil-law mechanism for managing state property, on the basis of the Law of Uzbekistan “On Joint-Stock Companies and Protection of Shareholders’ Rights” (No. ZRU-370) and the corporate-governance reform of 2024. It analyses the governing bodies of the company — the general meeting of shareholders as the supreme body (Art. 58), the supervisory board (Arts. 74–78) and the executive body (Art. 57) — together with the committee of minority shareholders, the audit commission and the newly introduced corporate secretariat. Particular attention is paid to the specifics of state participation, where the state acts as a shareholder through the State Assets Management Agency. The study identifies civil-law problems — the state-as-shareholder, minority protection, the liability of directors, the separation of ownership and regulation, and board independence — and proposes directions for their resolution in line with international standards.
Keywords: Corporate governance, joint-stock company, state participation, general meeting of shareholders, supervisory board, minority shareholders, corporate secretariat, state property.